SURROGATION IN PERPECTIVE LAW OF HUMANITARIAN PARADIGM - Yovita Arie Mangesti (Surakarta Law and Society Journal, 2020)
Surrogation arises as a result of the development of reproductive technology science with techniques embryo transfer and in vitro fertilization (IVF) techniques. The existence of a surrogate mother both for altruistic and transactional motives have implications for the problem law. Some countries provide different regulations on surrogation. This writing is the Reform-oriented research, which confirms that surrogation does not meet the rules humanitarian values, so the need for reconstruction of health laws against the rules concerning the institutionalization of human organs, reproduction outside of natural pregnancy, the provision of sufficient spare embryos and criminalization policies against advocates, perpetrators and surrogate mother in order to achieve justice and legal certainty. Keywords: surrogation, medicolegal, humanitarian paradigmatic law.